Development of Mobile Learning Based on Android Using Smart Apps Creator in Informatics Lessons of Grade XI in MA Negeri 2 Samarinda - Nur Raudah Datun Nisa; Fahmi Romisa (TEPIAN, 2025)
In the rapidly developing digital era, Indonesia has shown significant progress in the use of technology, including in the world of education. Technology is used to facilitate various learning activities, such as accessing information, supporting learning activities, and facilitating tasks by teachers. However, the application of technology in education still faces several challenges, such as the implementation of the Independent Curriculum and limited facilities and infrastructure. Therefore, this study aims to develop mobile learning media and then assess the feasibility of the product through assessments from material experts, media experts and responses from teachers and students. The method used in this study is R&D (Research and Development) with the 4D model (Define, Design, Development, and Disseminate). With the results of the mobile learning feasibility test by one material expert with an average score of 94% with the criteria "very feasible". The results of the mobile learning feasibility test by three media experts with an average score of 93%, 92%, 99% with the criteria "very feasible". If the average score of the three validators is averaged, it gets a score of 95% with the criteria "very feasible". The level of feasibility of mobile learning based on the results of the validation of materials and media obtained an average of 94% with the criteria of "Very Feasible" which states that mobile learning is very feasible and valid for use. can be seen and the media display is 94%. After being processed, the overall average is 95% with the criteria of "Very Good". While the average results of student responses, the value of two aspects, namely the material aspect is 91% and the media display is 93%. After being processed, the overall average is 92% with the criteria of "Very Good". Therefore, the android-based mobile learning product in informatics lessons for class XI MA Negeri 2 Samarinda is very feasible to use in the learning process to be more effective, interactive, and flexible, so that it can increase student motivation and learning outcomes.